Resolving Sub-Cycle Overvoltage Issue in Solar and Type-4 Wind Farms Employing Low Voltage Ride Through - Shah Mohazzem Hossain; Trupal Patel; Sukumar Brahma (IEEE Access)
Over the past few years, transmission grid in the USA has seen numerous unintentional tripping events of large-scale inverter based resources (IBRs). These trippings were primarily caused by non-standard settings and certain fault ride through controls implemented in the inverters, resulting in ‘subcycle overvoltage’ at the inverter terminals while recovering from a fault event. This paper first recreates the sub-cycle overvoltage scenario using a validated scaled farm model based on a real-world renewable farm. Using the simulation results and physics-based hypotheses, it identifies the root cause of the problem. Then, from mathematical analysis of the post-fault waveforms it proposes a control-based solution to comprehensively resolve this overvoltage issue in solar farms and in Type-4 wind farms. The solution logic is successfully implemented on a real-time platform. The solution, which is triggered by the dominant oscillation frequency in the post-fault voltage waveforms, and regulates the reactive power to successfully counter the rise of subcycle overvoltage, requires no hardware modifications, and can be implemented as a firmware upgrade in existing inverter controllers that are susceptible to the overvoltage-induced trippings.